Cheating alone and in teams - Alexander Dilger (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2021)
There is a reward for a project that can be increased through ability, effort, and cheating. This is analysed for one agent and a team of two. As an extension, a preference for honesty is added, which can prevent cheating but not without limit and not so easily in the team context. – – Es gibt für ein Projekt eine Belohnung, die durch Fähigkeit, Anstrengung und Betrug gesteigert werden kann. Dies wird für einen Agenten und ein Zweierteam analysiert. Als Erweiterung wird eine Präferenz für Ehrlichkeit hinzugefügt, die Betrug verhindern kann, aber nicht unbegrenzt und nicht so leicht im Teamkontext.
Keywords: D82; K42; Z20; Z22; 650